2015
DOI: 10.1111/jfbc.12201
|View full text |Cite
|
Sign up to set email alerts
|

Identification of β-Glucosidase Activity of E nterococcus Faecalis  CRNB-A3 in Airag and Its Potential to Convert Ginsenoside Rb1 from Panax Ginseng

Abstract: The objectives of this study were to isolate the lactic acid bacteria (LAB) exhibiting β‐glucosidase activity from Airag, and investigate the hydrolytic activity of the enzyme on saponin (Korean ginsenoside). Of the 33 types of LAB with positive reactions (β‐glucosidase) in the Esculin Iron Agar test, one LAB (CRNB‐A3) was found to have high hydrolytic activity for ginsenoside Rb1. 16S rDNA analysis revealed that CRNB‐A3 was Enterococcus faecalis (99.9% homology). The optimum temperature and pH for growth of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…β‐glucosidase activity increased by 5.0 times (174.3 ± 15.8 U g −1 in group A) and 5.4 times (182.9 ± 16.7 U g −1 in group B) compared with the control group at 36 h of koji making (Figure 1d). Differences between the experimental group and the control group may be attributed to the addition of NSTLAB‐LE during koji making, considering that previous studies have found that these two bacterial species can produce β‐glucosidase (Gouripur & Kaliwal, 2017; Renchinkhand et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…β‐glucosidase activity increased by 5.0 times (174.3 ± 15.8 U g −1 in group A) and 5.4 times (182.9 ± 16.7 U g −1 in group B) compared with the control group at 36 h of koji making (Figure 1d). Differences between the experimental group and the control group may be attributed to the addition of NSTLAB‐LE during koji making, considering that previous studies have found that these two bacterial species can produce β‐glucosidase (Gouripur & Kaliwal, 2017; Renchinkhand et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Bifidobacterium longum (content 6%) and Enterococcus sp. (content 6%) also have been reported to be involved in the deglycosylaiton of PPD-type ginsenosides [ 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bifidobacterium longum (content 6%) and Enterococcus sp. (content 6%) also have been reported to be involved in the deglycosylaiton of PPD-type ginsenosides [64,65]. Similarly, the incubation of diglycosylated PPT-type ginsenosides, GRe, GRf, and GRg1 with LAB produced GRh1.…”
Section: Lab-mediated Metabolism Of Ginsenosidementioning
confidence: 92%
“…Of these methods, enzymatic conversion is the most desirable one for production of particular ginsenosides ( Kim et al , 2005 ). β-glucosidase produced by various microorganisms such as Lactobacillus plantarum CRNB22 ( Renchinkhand et al , 2015 ), Enterococcus faecalis CRNB-A3 ( Renchinkhand et al , 2016 ) and Microbacterium sp. ( Cheng et al , 2008 ) has been used for the production of biotransfomed ginsenosides.…”
Section: Introductionmentioning
confidence: 99%